Reallocating time spent in sleep, sedentary behavior and physical activity and its association with pain: a pilot sleep study from the Osteoarthritis Initiative. Issue 12 (December 2018) - Song, J.; Dunlop, D.D.; Semanik, P.A.; Chang, A.H.; Lee, Y.C.; Gilbert, A.L.; Jackson, R.D.; Chang, R.W.; Lee, J.
Summary: Objective: Being physically active has broad health benefits for people with osteoarthritis (OA), including pain relief. Increasing physical activity (PA) requires reducing time in other behaviors within a fixed 24-h day. We examined the potential benefits in relation to pain from trading time in one type of wake or sleep behavior for another. Method: In this cross-sectional study, we used isotemporal logistic regression models to examine the estimated effect on pain from replacing time in one behavior with equal time in another, controlling for sociodemographic and health factors. Stratified analysis was conducted by the report of restless sleep. Sleep and wake behaviors [sedentary behavior (SB), light PA, moderate PA] were monitored by accelerometer in a pilot study of 185 Osteoarthritis Initiative (OAI) participants. Outcomes were bodily pain interference and knee pain. Results: Moderate PA substituted for an equivalent time in sleep or other types of wake behaviors was most strongly associated with lower odds of pain (bodily pain interference odds reduced 21–25%, knee pain odds reduced 17–20% per 10-min exchange). These beneficial associations were particularly pronounced in individuals without restless sleep, but not in those with restless sleep, especially for bodily pain interference. Conclusion: Interventions promoting moderate physical activities may be most beneficial to address pain among people with or at high risk for knee OA. In addition to encouraging moderate-intensity PA, pain management strategies may also include the identification and treatment of sleep problems.